LC-ESI-MS/MS method for oxidative stress multimarker screening in the exhaled breath condensate of asbestosis/silicosis patients - Syslová, K; Kačer, P; Kuzma, M; Pankrácová, A; Fenclová, Zdeňka; Vlčková, S; Lebedová, J; Pelclová, D (Journal of breath research, 2010)
The sensitive assay method was developed for a parallel, rapid and precise determination of the most prominent oxidative stress biomarkers: 8-iso-prostaglandin F(2α) a lipid oxidation biomarker, o-tyrosine an amino acid oxidation biomarker and 8-hydroxy-2'-deoxy-guanosine a nucleic acid oxidation biomarker. The method consisted of a pre-treatment part, freeze drying (lyophilization), serving the purpose of biomarkers concentration from the exhaled breath condensate and detection method LC-ESI-MS/MS, where the selected reaction-monitoring mode was used for its extremely high degree of selectivity and the stable-isotope-dilution assay for its high precision of quantification. The developed method is characterized by the following parameters: the precision was higher than 84.3% and the mean accuracy (relative error) was determined lower than 11.6%. The method was tested on samples obtained from patients diagnosed with asbestosis and silicosis, occupational diseases induced by oxidative stress, and then compared with samples from healthy subjects. The difference in biomarkers' concentration levels found between the two groups was statistically significant.
Keywords: Adult; Male; Breath Tests; silikóza; lidé; Humans; Young Adult; Biomarkers; hmotnostní spektrometrie s elektrosprejovou ionizací; Freeze Drying; azbestóza; chromatografie kapalinová; mužské pohlaví; Spectrometry, Mass, Electrospray Ionization; dospělí; mladý dospělý; Chromatography, Liquid; Oxidative Stress; Silicosis; biologické markery; oxidační stres; ženské pohlaví; lyofilizace; Female; dechové testy; Asbestosis